الخالدية بين الدعوة إلى الإصلاح والبعد الثوري الاستقلالي - قرين, مولود (جامعة الوادي - University of Eloued, 2022)
رغم ما كتب عن الأمير خالد، إلا أن نشاطه السياسي المميز في تاريخ الحركة الوطنية الذي شكل ظاهرة فريدة من نوعها جعلت البعض يسميها بالحركة الخالدية فهو في حاجة ماسة إلى مزيد من البحث، ولعلّ أهم إشكالية لازالت قائمة إلى يومنا هذا هي طبيعة حركته، فهل هي مجرد حركة إصلاحية في إطار الشرعية الفرنسية ؟، أم أنها حركة ذات أبعاد استقلالية؟. هذا ما ستحاول هذه الدراسة مناقشته انطلاقاً من كتابات الأمير، اعتمادا على المنهج التحليلي. توصلت الدراسة إلى عدة استنتاجات، لعلّ أهمها: واقعية الأمير خالد في نضاله، ففي الفترة الممتدة (1913م-1919م) لماّ كان نقيب في الجيش الفرنسي، تمحورت محاضراته حول التعبير المحتشم عن ما يعيشه المسلم الجزائري من أوضاع مزرية ، ولكن بعد نهاية الحرب العالمية الأولى، وما أفرزته من نتائج محلياً ودوليا حاول الأمير خالد استغلال الفرصة، ودخل معترك الحياة السياسية، باعتبار يجب أن يكون من داخل مؤسسات الإدارة الاستعمارية نفسها، وبالتوازي مع ذلك قام بعمل فردي حر، مراهناً على الصحافة (الإقدام)، والعمل الجمعوي، والمسرح. إضافة إلى فقد توصلت الدراسة إلى أن الحركة الخالدية بقدر ما كانت حركة إصلاحية، إلا أنها كانت ذات أبعاد ومرامي استقلالية تجسدت خاصة في عريضته إلى الرئيس ويلسن، وهريو ، وكذلك في الدور الفعال الذي قام به قبل تأسيس نجم شمال إفريقيا. This study will attempt to discuss the problem of Prince Khaled's movement, is it a purely reformist movement, or does it have revolutionary dimensions, based on the writings of the Prince, relying on the study's analytical method. The study reached several conclusions, perhaps the most important of which are: Prince Khaled’s realism in his struggle. During the extended period (1913-1919) when he was a captain in the French army, his lectures focused on the modest expression of the miserable conditions of the Algerian Muslim, but after the end of the First World War. And the results it produced locally and internationally, Prince Khaled tried to take advantage of the opportunity, and entered the battlefield of political life, as it must be from within the institutions of the colonial administration itself, and in parallel with that, he carried out individual free work, betting on the press (performance), collective action, and theatre. In addition, the study concluded that the Khalidi movement was as much a reformist movement, but it had dimensions and goals of independence embodied especially in his petition to President Wilson and Hario, as well as in the active role he played before the establishment of the North African Star.
دراسة تحليلية نقدية في أدبيات الأمير خالد
مقال
Keywords: الأمير خالد ; الحركة الخالدية ; جريدة الإقدام ; جمعية الأخوة ; التمثيل النيابي; Prince Khaled; Khalidiya movement; Elikdam newspaper; fraternity association; Parliamentary representation